PENERAPAN PRINSIP UTAMA GOOD GOVERNANCE PADA LAPORAN KINERJA INSTANSI PEMERINTAH DI BAPPEDA KABUPATEN SIDOARJO - Setiyowati, Mita Dwi; Reviandani, Oktarizka (Jurnal Progress Administrasi Publik, 2024)
Accountability for bureaucratic performance is a desired condition in state administration in accordance with Presidential Decree no. 81 of 2010. Bappeda Sidoarjo Regency as a regional government agency has an obligation to realize accountability for bureaucratic performance. Apart from that, accountability for bureaucratic performance in the Sidoarjo Regency Bappeda also encourages the realization of good governance in accordance with the main principles of good governance. One form of realizing the main principles of good governance in the Sidoarjo Regency Bappeda is the annual Government Agency Performance Report (LKjIP). The aim of this research is to find out how the main principles of good governance are implemented in the performance report of the Sidoarjo Regency Bappeda. The descriptive qualitative research method is the research method used in this research with research results through analysis of LKjIP documents, interviews and observations of employees who have authority in that section. The research results show that the Sidoarjo Regency Bappeda has implemented the main principles of good governance in administering regional government affairs. The four main principles of good governance that exist really support the Sidoarjo Regency Bappeda, especially in transparency to the public. However, there are still several main principles of good governance that need to be further optimized to increase the level of public trust in the Sidoarjo Regency Bappeda as a regional government agency that carries out regional government affairs, especially in regional planning and development.   Keywords: Good Governance; LKjIP; Bureaucracy Performance